Estimated strain coverage of serogroup B meningococcal vaccines: A retrospective study for disease and carrier strains in Greece (2010–2017). Issue 11 (12th March 2021) - Tzanakaki, G.; Xirogianni, A.; Tsitsika, A.; Clark, S.A.; Kesanopoulos, K.; Bratcher, H.B.; Papandreou, A.; Rodrigues, C.M.C.; Maiden, M.C.J.; Borrow, R.; Tsolia, M.
Abstract: Invasive meningococcal disease (IMD) is associated with high case fatality rates and long-term sequelae among survivors. Meningococci belonging to six serogroups (A, B, C, W, X, and Y) cause nearly all IMD worldwide, with serogroup B meningococci (MenB) the predominant cause in many European countries, including Greece (~80% of all IMD). In the absence of protein-conjugate polysaccharide MenB vaccines, two protein-based vaccines are available to prevent MenB IMD in Greece: 4CMenB (Bexsero™, GlaxoSmithKline), available since 2014; and MenB-FHbp, (Trumenba™, Pfizer), since 2018. This study investigated the potential coverage of MenB vaccines in Greece using 107 MenB specimens, collected from 2010 to 2017 (66 IMD isolates and 41 clinical samples identified solely by non-culture PCR), alongside 6 MenB isolates from a carriage study conducted during 2017–2018. All isolates were characterized by multilocus sequence typing (MLST), PorA, and FetA antigen typing. Whole Genome Sequencing (WGS) was performed on 66 isolates to define the sequences of vaccine components factor H-binding protein (fHbp), Neisserial Heparin Binding Antigen (NHBA), and Neisseria adhesin A (NadA). The expression of fHbp was investigated with flow cytometric meningococcal antigen surface expression (MEASURE) assay. The fHbp gene was present in-frame in all isolates tested by WGS and in 41 MenB clinical samples. All three variant families of fHbp peptides were present, with subfamily B peptides (variant 1) occurring in 69.2% and subfamily A in 30.8% of the samples respectively. Sixty three of 66 (95.5%) MenB isolates expressed sufficient fHbp to be susceptible to bactericidal killing by MenB-fHbp induced antibodies, highlighting its potential to protect against most IMD in Greece.